THE ROLE OF ECONOMIC AND DIGITAL FACTORS IN COMBATING CORRUPTION - Олександра Кубатко; Діана Харченко; Владислав Півень; Дмитро Литвиненко (Економіка та суспільство, 2023)
This article is devoted to the investigation of the impact of economic and digital factors on anti-corruption policy. The paper considers the main causes of corruption, its negative impact on social processes and political stability, and ways to overcome it. It was emphasized that corruption weakens the economic growth of countries, reduces citizens' trust in the government. Bribery, its scale, dynamics and specification are a consequence of political, social and economic problems of countries, and the world has not yet come up with a single recipe for fighting corruption. Research revealed that digitization can significantly increase the openness, publicity and transparency of public administration, identify corrupt connections, schemes and relationships, optimize anti-corruption activities of law enforcement agencies and limit the opportunities for corrupt officials. In the period of a post-war recovery Ukraine will need significant reforms, especially in the anti-corruption sphere, so there is an objective scientific and practical demand for a comprehensive study of anti-corruption issues. During the writing of the article the methods of theoretical and practical research were used, including the method of the panel data analysis. The empirical results have proved that the promotion of digital economy can significantly minimize corruption. For example, the digital economy can help tackle corruption by enabling greater transparency, reducing opportunities for corrupt practices, and empowering citizens to participate in the fight against corruption. As technology continues to evolve, there will likely be even more opportunities to leverage the digital economy to combat corruption and promote transparency and accountability. Based on the obtained resuts, the recommendations for tackling corruption were suggested.